PEMERIKSAAN PERKARA PERDATA SECARA PRODEO - Dian Latifiani (Fakultas Hukum Universitas Wahid Hasyim, 2012)
The purpose of law is to protect the public and provides justice and harmony in the country, besides everyone also has the right to the recognition, guarantees, protection and legal certainty of fair and equal treatment before the law. In order to hold a judicial process that is fast, cheap, simple and open, it must be carried out regardless of the position, group or the social status of a person. In public life, legal dispute among the community members can happen. If any conflict arises among the community, a lawsuit will show up. For the shake of the establishment of a harmonious community life, any lawsuit arising shall get a completion. The best completion is by implementing deiberative decision-making to reach consensus. However , if it does not succeed, in accordance with state law, the case should be resolved through the court.Party that feels his or her right has been violated, may file a lawsuit to the competent court to adjudicate the case. The purpose of it is to get right protection as well as legal protection from the court. According to the principle of civil law, there is cost to file a lawsuit. This is in accordance with article 2 of paragraph 4 of the Law No. 48 of 2009 about the Powers of the Judiciary and article 121 of paragraph 4 HIR. However , for public members who are not able to pay for the lawsuit, should also get the same legal services, even societies like this may get legal assistance to litigate. One form of legal assistance that can be given to underprivileged communities in litigation of the civil case is: the allowance for litigating civil cases without cost (Prodeo). This is in accordance with the article 237 to 245 HIR that mention “those who are willing to be involved in law cases, either as plaintiffs or defendants, but they are unable to pay the cost, can litigate the lawsuit with the permission of not paying the cost”.Keywords: Civil Casses, Prodeo, Investigation.